Methods Of Using Innovative Technologies in Developing Acmeology Of School Music Teachers - Mustafoyev Bakhtiyor Ibragimovich (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2025)
This article analyzes the role of innovative technologies in developing acmeological abilities of school music teachers. The study used questionnaires, tests and observation methods to study the activities of 60 music teachers. The results showed that innovative technologies are an effective tool for increasing the professional growth and creative potential of teachers. It also identified the need for further development of technical support and methodological knowledge. The article concludes with recommendations and practical suggestions.